Liquidity Risk Management and Financial Performance of Conventional Commercial Banks in Malaysia - S/O Manual, Vikneswaran; Hui Shi, Chin; Zaleha Abdul Rashid, Siti; Zaleha Abdul Rashid, Siti (International Journal of Psychosocial Rehabilitation, 2020)
This study determines the relationship between liquidity risk indicators and financial performance of Malaysian conventional commercial banks with the eventual objective to advice policies to improve the management of liquidity risk in Malaysia banks. Malaysia banking sector definitely will gain valuable benefit from this study because liquidity risk management and bank performance are the significant determinant of the development, survival, sustainability, growth and performance of Malaysian banking system. The liquidity risk indicators used in this study include the cash reserves, customer deposit, liquidity gap, liquidity ratio and nonperforming loan; while the financial performance is determined by return on assets and return on equity as the dependent variables. The secondary data was retrieved from the published annual reports of eight (8) locally owned conventional bank in Malaysia for the 10-year period from 2008 to 2017. Balanced panel fixed-effect regression models are applied to assess the influence of these five (5) liquidities risk indicators on financial performance of all local conventional banks in Malaysia. Estimates are performed using the Estimated Generalized Least Squares (EGLS) weight of cross-sectional seemingly unrelated regression (SUR). The results reveal that cash reserves, customer deposit, liquidity gap, and liquidity ratio have a significant negative impact on financial performance; and nonperforming loan has a significant and positive effect on Malaysian bank profitability. However, the study found that the correlation between customer deposit and return on asset are insignificant. Furthermore, it also found that the cash reserve does not have any significant impact on the return on equity. The study discovered that the least influential factor is cash reserves, indicating that cash reserve had the least impact on banks’ earnings for Malaysian conventional banks. Conversely, liquidity ratio and liquidity gap are the most influential liquidity risk factors towards return on asset and return on equity, respectively.